2012
DOI: 10.1159/000341219
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence and Four-Year Caries Incidence in Finnish Adults

Abstract: This study assesses whether sense of coherence (SOC) predicts incidence of tooth decay over 4 years and the role of dental behaviours in explaining the effect of SOC on incidence of tooth decay. Data from 994 adults who participated in both the Health 2000 survey and the Follow-Up Study of Finnish Adults’ Oral Health were analysed for this study. At baseline, participants provided information on demographic characteristics, education level, the SOC scale and dental behaviours (tooth brushing frequency, dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…As expected, less frequent toothbrushing and more sugary soda drink consumption were associated with decayed teeth. Furthermore, there seemed not only to be a direct relationship between SOC and number of decayed teeth, SOC also appeared to be linked to oral health‐related behaviour, which in turn predicted dental caries, as has been suggested in previous studies …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As expected, less frequent toothbrushing and more sugary soda drink consumption were associated with decayed teeth. Furthermore, there seemed not only to be a direct relationship between SOC and number of decayed teeth, SOC also appeared to be linked to oral health‐related behaviour, which in turn predicted dental caries, as has been suggested in previous studies …”
Section: Discussionsupporting
confidence: 72%
“…Sense of coherence (SOC) is a salutogenic construct relating to the way an individual makes sense of the world (comprehensibility), has the required resources to respond to life events (manageability) and feels that these responses are meaningful and make sense (meaningfulness) . A stronger SOC has been associated with greater dental attendance, more frequent toothbrushing and fewer oral health‐related impacts . The research to date would suggest that salutogenic factors—such as SOC—could play an important role in improving dental access and oral health‐related behaviours and outcomes in adults.…”
Section: Introductionmentioning
confidence: 99%
“…The results elucidate that healthy choices for young adults are based on the amount and the content of the internal and external resources in the individual's life context and, more importantly, the individual's ability to use such recourses in a healthy direction, beneficial for general and oral health. The present results complement with new perspectives and understanding to the salutogenic concept of a sense of coherence (SOC) and could be discussed in relation to the results of previous studies using the SOC questionnaire in association with oral health in young adults/adolescents and adults . Associations between a high SOC and general health behaviour, better social competence, dealing with everyday matters and greater independence have recently been found in adolescents .…”
Section: Discussionmentioning
confidence: 80%
“…In elderly and adult populations, SOC was identified as a psychosocial determinant of oral health-related quality of life [Savolainen et al, 2005a;Boman et al, 2012;Machado et al, 2017], oral health-related behaviors, attitudes towards oral health, knowledge of dental caries [Savolainen et al, 2005b;Bernabé et al, 2009;Lindmark et al, 2011;Elyasi et al, 2015], and dental clinical status [Bernabé et al, 2010[Bernabé et al, , 2012Gupta et al, 2015;Davoglio et al, 2016;Possebon et al, 2017]. Other studies have shown a positive prospective relationship between strong SOC and better oral health-related quality of life among adolescents [Baker et al, 2010;Pakpour et al, 2018].…”
Section: Introductionmentioning
confidence: 99%